Quantifying College Students’ Bystander Behavior to Prevent Sexual Assault and Intimate Partner Violence: Can We Make Improvements? - Krauss, Alison (Journal of interpersonal violence, 2023)
Sexual assault and intimate partner violence (IPV) are prevalent on college campuses, and bystander intervention programs are often employed as a method for preventing such violence. Unfortunately, there are concerns about current strategies for the measurement and quantification of bystander behavior. Accounting for the opportunity to engage in bystander behavior is theorized to be important, but it remains unclear if doing so improves the validity of the measurement of bystander behavior. The current study compares four methods of quantifying bystander behavior when information about the opportunity to help is also available. First-year undergraduate students (n = 714) from three universities participated. Participants completed the risky situations subscale of the Bystander Behavior Scale, using a modified response scale to measure both bystander behavior and opportunity for such behavior. Measures of criterion variables theorized to be linked with bystander behavior (efficacy to intervene, responsibility to intervene, and moral courage) were also completed. Four types of bystander behavior scores were calculated: breadth, missed opportunity, offset, and likelihood. Likelihood scores, which reflect the likelihood of engaging in bystander behavior when presented with the opportunity to help, correlated more strongly with the criterion variables than other scores. Likelihood scores demonstrated added value in quantifying bystander behavior over other scoring methods. Findings from the current study add to the knowledge of how best to measure and quantify bystander behavior. Such knowledge has significant implications for research on correlates of bystander behavior and evaluations of bystander intervention programs for sexual assault and IPV prevention.